Multiple venous anastomoses decrease the need for intensive postoperative management in tamai zone I replantations - Deok Hyeon Ryu; Si Young Roh; Jin Soo Kim; Dong Chul Lee; Kyung Jin Lee (Archives of Plastic Surgery, 2018)
Background Venous anastomosis is an important component of digital replantation, but is not always feasible, as some cases require external bleeding to treat venous congestion in the replanted tissue. In the present study, we evaluated the relationship between the number of vein anastomoses and the survival rate of Tamai zone I replantations.